Genomic Analysis Reveals Heterogeneity Between Lesions in Synchronous Primary Right-Sided and Left-Sided Colon Cancer - Hu, Hanqing; Zhang, Qian; Huang, Rui; Gao, Zhifeng; Yuan, Ziming; Tang, Qingchao; Gao, Feng; Wang, Meng; Zhang, Weiyuan; Ma, Tianyi; Qiao, Tianyu; Jin, Yinghu; et al. (Frontiers in Molecular Biosciences, 2021)
Abstract Background: The synchronous primary right-sided and left-sided colon cancer (sRL-CC) is a peculiar subtype of colorectal cancer. However, the genomic landscape of sRL-CCs remains elusive. Methods: 28 paired tumor samples and their corresponding normal mucosa samples from 14 patients were collected from the Second Affiliated Hospital of Harbin Medical University from 2011 to 2018. The clinical-pathological data were obtained and the whole-exome sequencing was performed based on FFPE samples of these patients. And then, a comprehensive bioinformatic analyses were conducted. Results: The both lesions of sRL-CC present dissimilar histological grade and differentiation. Based on sequencing data, few overlapping SNV signatures, onco-driver genes mutations and SMGs were identified. Moreover, the paired lesions harbor different distribution of copy number variants and loss of heterozygosity. The clonal architecture analysis demonstrates that polyclonal origin of sRL-CC and inter-cancerous heterogeneity between two lesions. Conclusion: Our work provides evidence that lesions of sRL-CC share few overlapping mutational signature and CNVs and may originate from different clones.